Recent Herbal Trends against Fungal Infections: A Review - Rawat, Swati; Jain, Akansha; Jain, Shubham (Pharmacognosy Reviews)
Herbs have been one of the important and unique sources of medicines even since the dawn of human civilization. In spite of tremendous development in the field of allopathy during the 20th century, plants still remain one of the major sources of drug in the modern as well as traditional system of medicine throughout the world. Over 60% of all pharmaceuticals are plant-based. Plants and its phytoconstituents are used not only used to prevent but also used to cure various disorders. Various researches on plants all over the world either have been or have to be carried out for eradicating ailments. Most common of which is fungal infections, especially Mucosal Candidiasis caused by fungi Candida albicans. The incidence of fungal infections is increasing at an alarming rate, presenting an enormous challenge to healthcare professionals. This increase is directly related to the growing population of immunocompromised individuals, resulting from changes in medical practice such as the use of intensive chemotherapy and immunosuppressive drugs. The present study is a review on plants that have been found to have antifungal action against Candida albicans. Phytoconstituents isolated from various plants such as Echinacea purpurea, Foeniculum vulgare Miller, Mentha piperita L., Citrus limon, Lycopodium cernuum, Nigella sativa, Pallavicinia lyellii etc. had been investigated by various scientists and were found to have potent antifungal activity against Candida albicans and their various strains.
Keywords: Antifungal; Candida albicans; oropharyngeal candidiasis; vulvovaginal candidiasis